Molecular variants of multiple genes were revealed by whole-exome sequencing in PCOS patients with diabetes - Wang, Chenglin (Frontiers in Genetics, 2025)
ObjectiveTo screen for possible pathogenic mutations in polycystic ovary syndrome (PCOS) patients with diabetes and preliminarily explore the relationship between genotype and phenotype to offer a research basis for PCOS pathogenesis with diabetes.MethodsFour patients with PCOS and diabetes were recruited and their demographic and clinical data were collected. Genomic DNA was extracted from peripheral blood leukocytes of the study subjects. High-throughput whole-exome sequencing was conducted to identify candidate genes that could play a pathogenic role in PCOS with diabetes in Aiji Taikang. The sequencing data obtained were evaluated using a variety of bioinformatics tools. Verification of candidate sites was done by Sanger sequencing.ResultsBased on whole-exome sequencing, six mutations residing in three genes were detected in these four patients: (1) MUC4 located at Chr 3q29, (2) FSHD region gene 1 (FRG1)gene located at Chr 4q35.2, and (3) androgen receptor (AR) located at Chr Xq11-q12 were detected in these four patients (every patients had the 6 mutations). Of the six genetic mutations, an insertion/deletion (indel) mutation was found in the mucin 4 (MUC4) gene [MUC4:NM_018406.6:2/25:c.7701_7702insTCAGTATCCACAGGTCATGCCACCCCTCTTCATGTCACCGACACTTCC:p.(Ser2567_Ala2568insSerValSerThrGlyHisAlaThrProLeuHisValThrAspThrSer)], and an indel mutation in the AR gene (AR:NM_000044:exon1:c.173_174insGCAGCA:p. Q58delinsQQQ), while the other four were missense single-nucleotide polymorphisms (SNPs) located in FRG1 of uncertain significance (FRG1:NM_004477:exon8:c.T692C:p. L231P, FRG1:NM_004477:exon8:c.C728T:p.T243M, FRG1:NM_004477:exon8:c.C733A:p.L245M, FRG1:NM_004477:exon8:c.T734G:p.L245R). A Mucin 4 (MUC4) gene indel mutation was detected at the same site in four patients, which could be associated with endometriosis-related infertility. The AR gene indel mutation, AR:NM_000044:exon1:c.173_174insGCAGCA: p. Q58delinsQQQ was detected simultaneously in four patients.ConclusionWhole exome sequencing can quickly identify candidate genes for genes. Gaining an in-depth understanding of the AR mutations underlying PCOS with diabetes will deepen our understanding of the endocrine factors involved in the disease etiology, and provide potential targets for treatment.